Intensification of agriculture and livestock based on low carbon technologies in the Amazon and Atlantic Forest - Silveira, Júlia Graziela da (2022)
The Amazon and the Atlantic Forest are Brazilian biomes that have undergone intense land use and cover changes, marked by the loss of native forest and the expansion of agriculture and livestock. These are areas with potential use for intensification based on low-carbon technologies, but this change is still taking place slowly. Some factors need to be identified to guide promising solutions for this issue. Aiming at this, this study aimed to identify the land use and land cover in a historical series of 35 years in the Amazon and Atlantic Forest and describe the patterns of sustainable land use by producers who use this technique in the Amazon, identifying their characteristics and perceptions regarding the change developed in the farm. The statistics of the platform from the Annual Mapping Project for Land Use and Land Cover in Brazil (MapBiomas) were used in an annual historical series from 1985 to 2020. The analysis of land use and land cover changes indicates that the native forest of the Amazon was reduced by 44.53 million hectares (Mha), while pastures, agriculture and planted forest increased by 38.10, 6.06 and 0.26 Mha, respectively, over the 35 years. In the Atlantic Forest, for the same period, forest and pasture reduced by 0.99 and 11.53 Mha, respectively, while agriculture expanded by 8.06 Mha and planted forest by 2.99 Mha. Sustainable land use strategies, such as Integrated Crop-Livestock-Forest (ICLF) or Agroforestry Systems (AFS), can support increased agricultural production while recovering and preserving the environment. In view of this, we identified in the Amazon, the pattern of land use by farmers who adopt sustainable technologies, considering AFS and managed pasture monoculture (MP). The results were generated through interviews and analysis of qualitative and quantitative research that allowed the evaluation of producers in three states in the Amazon (Mato Grosso, Pará and Rondônia). In general, farmers in the Amazon are still risk averse and mainly implement MP. But when assessing the states in isolation, we realize that the producers in Pará and Rondônia are more approachable when it comes to moving to a diversified system. We did not find many differences in the profile of these producers, but we noticed that pasture adopters always have areas of larger properties and generally develop livestock as their main economic activity. On the other hand, AFS producers have smaller areas of property, conserve more forest and may have agriculture as the main activity of the property. Regional and local fitness, producer tradition and technology transfer can influence the decision of the adopted technology. There are great opportunities to improve agricultural and livestock practices with MP systems and AFS, demonstrated through improvements in farm income, productivity and environment. This evidence can be extrapolated to land use in the Atlantic Forest biome. However, we emphasize the need to consider regional characteristics, socioeconomic conditions and the perspectives of producers in the development of public policies and programs to encourage sustainable agriculture. Keywords: Sustainable Development. Agroforestry System. Crop-Livestock-Forestry Integration. Rural Producer.